2019
DOI: 10.3389/fpls.2019.00501
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Mild Salinity and Drought Synergistically Enhances Biomass and Grain Retardation in Wheat

Abstract: In the present study we analyzed the responses of wheat to mild salinity and drought with special emphasis on the so far unclarified interaction of these important stress factors by using high-throughput phenotyping approaches. Measurements were performed on 14 genotypes of different geographic origin (Austria, Azerbaijan, and Serbia). The data obtained by non-invasive digital RGB imaging of leaf/shoot area reflect well the differences in total biomass measured at the end of the cultivation period demonstratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Thus, observed earlier reduction in DB leaf related traits under severe drought treatment compared to salinity treatments could indicate that during the first 7 days salinity treatments did not prevent water uptake to the same extent as was the case in severe drought treatment. However, similarly to our findings, Paul et al (2019) found a higher reduction in biomass and leaf area under drought compared to salinity stressed wheat cultivars. Moreover, other measured traits (chlorophyll fluorescence parameters) indicate that salinity, as well as drought, caused significant stress to the basil plants already after 1 week.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, observed earlier reduction in DB leaf related traits under severe drought treatment compared to salinity treatments could indicate that during the first 7 days salinity treatments did not prevent water uptake to the same extent as was the case in severe drought treatment. However, similarly to our findings, Paul et al (2019) found a higher reduction in biomass and leaf area under drought compared to salinity stressed wheat cultivars. Moreover, other measured traits (chlorophyll fluorescence parameters) indicate that salinity, as well as drought, caused significant stress to the basil plants already after 1 week.…”
Section: Discussionsupporting
confidence: 91%
“… Liu et al (2014) found that the interaction of salt and drought stresses had a stronger inhibitory effect on the growth of Tamarix chinensis . Similar results were found in Triticum aestivum ( Paul et al, 2019 ), Elaeagnus angustifolia ( Chen et al, 2019 ) and Populus pruinosa ( Wang et al, 2018 ). Another remarkable phenomenon observed in Northeast China is soil alkalization ( Lin et al, 2017 ).…”
Section: Introductionsupporting
confidence: 74%
“…Farmers added that intensified droughts accelerated soil salinization, exacerbating the impact of erratic weather on food production. Some findings in the literature align with this suggestion that droughts worsen soil salinity, while salt, in turn, prohibits water uptake by plants (Paul et al, 2019;Corwin, 2020). To address this problem, Tanzanian research institutes developed a salt-tolerant version of the SARO variety, called SATO, which is becoming a necessity for farmers to be able to sustain food production.…”
Section: Intensive Paddy Farming With Hybrid Seeds As Adaptationmentioning
confidence: 70%